Polarization properties of a 2‐D split ring resonator and rod type metamaterial lens. Issue 9 (September 2014) - McGillivray, Duncan A.; Cravey, Robin L.; Dudley, Kenneth L.; Vedeler, Erik; Gupta, Mool C.
ABSTRACT The polarization state of microwave (MW) radiation transmitted through a 2‐D split ring resonator and rod metamaterial (MTM) lens is investigated. At a resonance frequency of 3.63 GHz, the 2‐D lens modifies the polarization state of the incident radiation. For Ey incident polarization, the transmitted wave exhibits elliptical polarization as well as a tilt in the principal axis. The ellipticity is dependent on the incident polarization angle. A Ex polarized incident MW is unaffected. Transformation of polarization properties plays an important role for manipulation and control of MW radiation, impacting existing applications and providing opportunities for novel MTMs‐based sensors and other applications. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2146–2150, 2014